2021
DOI: 10.1038/s41598-021-82266-5
|View full text |Cite
|
Sign up to set email alerts
|

Panel of serum miRNAs as potential non-invasive biomarkers for pancreatic ductal adenocarcinoma

Abstract: Early-stage diagnosis of pancreatic ductal adenocarcinoma (PDAC) is difficult due to non-specific symptoms. Circulating miRNAs in body fluids have been emerging as potential non-invasive biomarkers for diagnosis of many cancers. Thus, this study aimed to assess a panel of miRNAs for their ability to differentiate PDAC from chronic pancreatitis (CP), a benign inflammatory condition of the pancreas. Next-generation sequencing was performed to identify miRNAs present in 60 FFPE tissue samples (27 PDAC, 23 CP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 62 publications
0
31
0
1
Order By: Relevance
“…The comparative analysis of the identified miRNAs' influence on the ERα expression showed that miR-181a-2 demonstrates the maximal inhibitory activity (Figure 1a), and all following experiments were performed with the latter. The role of this miRNA in cancer progression is of great interest as its expression correlates with cell proliferation and with the survival of cancer patients [79][80][81].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative analysis of the identified miRNAs' influence on the ERα expression showed that miR-181a-2 demonstrates the maximal inhibitory activity (Figure 1a), and all following experiments were performed with the latter. The role of this miRNA in cancer progression is of great interest as its expression correlates with cell proliferation and with the survival of cancer patients [79][80][81].…”
Section: Resultsmentioning
confidence: 99%
“…following experiments were performed with the latter. The role of this miRNA in cancer progression is of great interest as its expression correlates with cell proliferation and with the survival of cancer patients [79][80][81].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported speci c upregulation or downregulation of serum miRNAs in certain types of cancers [9,[11][12][13][14][15][16][17][18][31][32][33][34][35]. Yet, few studies have investigated the potential of serum miRNAs as a general cancer screening markers across multiple cancer subtypes [6,19].…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study also demonstrated that these five miRNAs had significantly different levels between the serum of patients with CP and those with earlystage PDAC. This panel has the potential to become part of a multicomponent screening panel of CP patients for PDAC [63]. One of the most promising and investigated miRNAs in PDAC is miR-21-5p, which is also overexpressed in many other types of cancer [64].…”
Section: Circulating Mirnas and Their Diagnostic Significance In Early-stage Pdacmentioning
confidence: 99%